Folgen des Thronfolgers Die erste Rezeptionswelle des Franz-Ferdinand-Romans - Ladislav Futtera (Brünner Beiträge zur Germanistik und Nordistik, 2021)
This paper deals with the early reception (using the concept of the "early wave of reception" [prvotní recepční vlna] suggested by Dalibor Tureček) of Ludwig Winder's novel Der Thronfolger which was published in November 1937 in Switzerland and in the spring of 1938 in Czechoslovakia in Czech translation. The reviews of the novel are researched in both the German-speaking and the Czech-speaking contexts in Czechoslovakia, in Austria and in the German-speaking exile, especially in Switzerland. Special attention is paid to the strategies of the publisher and the author when presenting the work to the public.